تحليل أوجه التشابه والاختلاف بين الفيلم المصري "علي بابا والأربعين حرامي" والفيلم الماليزي "علي بابا بوجانج لابوك": دراسة مقارنة - Mohd Adil Mufti Bin Mohamad Samsudin
The Egyptian film “Ali Baba and the Forty Thieves” and the Malaysian Film “Ali Baba Bujang Lapok”, both these films are inspired by the story of “Ali Baba and the Forty Thieves” contained in the great tale, The Tale of One Thousand and One Nights. This research aims to show the similarities and differences that exist between both works in terms of characters, plot, events and environment. This research deals with arm-rest study methodology by taking both the Egyptian and Malaysian films as the main source, and then comparing them according to the French School of Comparative Literature in order to reach the results. The research found that there are similarities and differences between the two works in terms of characters, plot, events, and environment. Among those similarities are the similarity in the title of the story that use male name, the similarity in the conflict of the woman, the similarity in the role of Qasim Baba’s wife that put some stickers in the scale, the similarity in the spatial environment and others. Among those differences, they are the difference in the number of characters, the difference in the middle of the plot, the difference of the password to open and close the cave, the difference in the spatial environment and others.